Pemanfaatan Flipbook dalam Mengemas Materi Teks Deskripsi Berwawasan Budaya Daerah Kelas X: Utilization of Flipbooks in Packaging Descriptive Text Material with Regional Cultural Insights for Class X - Suherlinda Suherlinda; Malan Lubis; Abdurahman Adisaputera; Wisman Hadi; Mara Untung Ritonga; Syairal Fahmy Dalimunthe; Safinatul Hasanah Harahap (Edu Cendikia: Jurnal Ilmiah Kependidikan, 2026)
Indonesian language learning for tenth-grade high school (SMA/SMK) students still faces challenges in presenting descriptive text material that is engaging, interactive, and contextual. The material is generally presented through conventional printed textbooks and lacks integration of interactive visual elements and local wisdom. This condition results in low student interest and understanding of the material. In fact, various studies have shown that integrating digital technology and regional cultural content can increase student engagement and learning experience. However, the development of interactive flipbooks that combine descriptive text with regional cultural insights remains limited. This study aims to develop digital flipbook learning media with regional cultural insights for tenth-grade students. The method used is research and development (R&D) with the ADDIE model, which includes the stages of analysis, design, development, implementation, and evaluation. The feasibility test was conducted through validation by media and material experts, as well as user testing with students. The results showed that the developed flipbook media received a very feasible rating from media and material experts. In addition, student responses were very positive, indicating that this media is interesting, easy to use, and helps improve students' understanding of descriptive text. Digital flipbooks with regional cultural insights are effective and suitable as learning media for descriptive texts in class X. They can integrate digital literacy with efforts to preserve local culture in the learning process.